Effect of D-Mannose on Gene Expression of Neuraminidase Produced from Different Clinical Isolates of Pseudomonas aeruginosa (Baghdad Science Journal, 2019)
The present work aimed to investigate the neuraminidase (nan1) gene expression in 32 different clinical isolates of Pseudomonas aeruginosa to explore the role of the enzyme in different types of infection and might give a better understanding of host cell-pathogens interaction. In addition, the effect of monosaccharide D-mannose on neuraminidase gene expression in eight isolates was studied by utilizing a reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The results demonstrated that the highest expression of nan1 gene was in otitis samples (208,913.81) which were significantly higher than that from other infections (P < 0.01). While, the concentrations of gene copies obtained from urine, sputum and burns samples were 93,535.34, 92,254.64 and 74,029.63respectively. While the least expression in wound samples (32,017.06). This suggests that neuraminidase in ear samples might be more virulent and invasive followed by that from urine, sputum, burns and wounds samples. The considerable interest of addition D-mannose significantly reduced the rate of neuraminidase activity reached fivefold in some isolates. This indicates that D-mannose down regulates nan1 gene expression. Hence, this sugar could be used in the development of potential new antibacterial agents where it acts as a competitive neuraminidase inhibitors.